The Influence of Teacher Interaction Patterns in Learning on Student Learning Motivation in the Office Management and Business Services Department of YAPMI Makassar Vocational School - Kyky Amalia; Haedar Akib; Sirajuddin Saleh (ASHA Publishing, 2026)
This study aims to identify the interaction patterns of teachers in the Office Management and Business Services department at SMK YAPMI Makassar and their influence on student learning motivation. This study is quantitative with a focus on two main variables, namely teacher interaction patterns and student learning motivation. A questionnaire consisting of two main parts, namely teacher interaction patterns in education and student learning motivation, was used to collect data. The results of the study indicate that there is a positive relationship between teacher interaction patterns and student learning motivation at SMK YAPMI Makassar. However, this relationship is relatively weak with a correlation coefficient value close to zero, namely r squared of 0.088. This means that only 8.8% of the variation in the dependent variable (student learning motivation) can be explained by teacher interaction patterns, while 91.2% of the dependence is influenced by other factors not included in this study. The level of student learning motivation at SMK YAPMI Makassar is classified as excellent, with a percentage reaching 82.93%. Student learning motivation is measured through three main indicators: (1) persistence in completing tasks, (2) persistence in facing challenges during the learning process, and (3) the ability to express and defend opinions actively during the learning process. These findings indicate that teacher interaction is not the only determining factor, but it still plays an important role in shaping student learning motivation. Therefore, improving the quality of interaction between teachers and students needs to receive more attention in an effort to improve learning outcomes and active student participation in class. This study also opens up opportunities for further research that can explore other factors that influence student learning motivation more comprehensively, such as classroom environment, teaching methods, and peer interactions.